STUDI KUANTITATIF PEMANFAATAN SISTEM INFORMASI KEUANGAN DAERAH DAN GOOD GOVERNANCE TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH - Erika Yuliana Putri; Siti Sundari (Program Studi Akuntansi Institut Teknologi dan Bisnis Asia Malang, 2025)
This study aims to examine the impact of the utilization of the Regional Financial Information System (SIKD) and the implementation of good governance principles on the quality of local government financial statements The population of this study consists of 123 employees working at the Regional Secretariat, specifically within the Office of the Regent of Gresik Regency. The sampling technique employed is purposive sampling based on specific criteria, resulting in a total sample of 32 respondents. Data analysis was conducted using the SmartPLS software. The findings indicate that both the use of SIKD and the application of good governance have a significant relationship with the quality of local government financial statements.